The Former Yugoslav Republic of Macedonia : Toward an Education Strategy for the Twenty-First Century - World Bank (Washington, DC, 2013)
This note identifies major challenges now facing the Macedonian education system and suggests policies and programs for addressing them. Its primary function is to inform the representatives of the Government as well as other political leaders and stakeholders, in a continual dialogue with the World Bank, about the Bank team's position on the main challenges and policy options, which Macedonian education policy makers may consider. Given the past ethnic conflict and current political situation, Macedonia likely will require a significant increase in donor support in upcoming years to remedy some underlying social and economic problems and to simplify rehabilitating the school infrastructure. It is important that donor activities fit into a strategy and a follow-up policy framework to be agreed upon with the Government. Based on the country assistance strategy signed by the Government and the Bank, the next education project's preparation is underway and is planned to be effective by early 2004. This education policy note therefore intends to offer a coherent policy basis for the government's evolving strategy and to establish a basis for the project preparation, for other donor activities in education and for subsequent discussions on the opportunities and options of future Bank support in education. The note focuses on (i) the main strength and potential of education in assisting the country's overall social and economic development; (ii) the main challenges education faces in terms of the system's management, structure and performance; (iii) the opportunities and policy options for reforming the education system; (iv) the main political risks that reformers need to take into account; and (v) general reform options the government strategy could take into account.